Kandungan Boraks dan Formalin Pada Sempol Ayam Yang Beredar Di Sekolah Dasar Kecamatan Sukolilo Surabaya - Hardinata, Taufan; Djauhari, Arlin Besari (Universitas Dr Soetomo, 2018)
Chicken Sempol is a snack food that lately selected by all of ages, especially by elementary school student because it easily found in elementary schools at Surabaya and affordable prices. Sempol is a snack that the ingredients and the processing such as meatballs but only the process and the servings is different because it stabbe with a stick like sate and served after fried dipped earlier in egg whisk.Sempol chicken circulating at Surabaya suspected contain dangerous Food Additives such as borax and formaldehyde so it should be tested. Research on sempol assay was be done on chicken sempol were sold in 23 elementary schools in Sukolilo district, Surabaya got 26 chicken sempol traders. The results showed that only one chicken sempol sold did not contain borax and formalin (4,348 %), while 25 chicken sempol from different traders in different elementary schools are also contained borax and formalin (95,652 %). Borax and formaldehyde were qualitatively assay, the assay of borax based on the color change of curcumin paper and the assay of formaldehyde is done by determining the KMnO4 solution to determine the pink disappearance of the KMnO4 solution. Keywords: borax; formalin; sempol chicken; Sukolilo